Improving pronunciation through the use of karaoke in an adult english class (2009)
Students often have difficulty and experience lots of problems with pronunciation in English. This article is based on a research project which intended to show how students can improve their pronunciation through the use of karaoke in their English class. By using karaoke, the teacher designs activities and involves students to improve their pronunciation. Students’ progress is analyzed in order to arrive at a conclusion of the effectiveness of the karaoke sessions. It is also shown that the karaoke classes offer a lot of fun and creativity while students cooperate with each other to achieve their pronunciation goals. Key words: Improving pronunciation, karaoke activities Los estudiantes frecuentemente tienen dificultades y experimentan muchos problemas al pronunciar en inglés. Este artículo se basa en un trabajo investigativo que buscó mostrar cómo los estudiantes pueden mejorar su pronunciación mediante el uso del karaoke en sus clases de inglés. Con el uso del karaoke, el profesor diseña actividades e involucra a los estudiantes en el mejoramiento de su pronunciación. Se analiza el progreso del estudiante para alcanzar una conclusión sobre la efectividad de las sesiones de karaoke. También se muestra que las clases de karaoke ofrecen mucha diversión y creatividad mientras los estudiantes cooperan entre ellos para alcanzar sus metas en cuanto a la pronunciación. Palabras clave: Mejoramiento de la pronunciación, actividades con karaoke